Kinetika Adsorpsi Phenol Dalam Air Dengan Arang Tempurung Kelapa - Panut Mulyono; Wisnu Madha Kusuma (Forum Teknik, 2010)
Abstract Phenol  is  a hazardous  chemical  which  usually  contained  in  the  wastewater  from  some industries, such as oil refineries, coal processing, and plastics. Phenol is dangerous substance to a microorganism although in low concentration in wastewater. According to the United State Environmental  Protection  Agency,  the  maximum  concentration of  phenol  in wastewater  is  1 ppm.  This  requirement  is  lower  than  the  concentration  of  phenol  in  normal  wastewater discharged from industries that is 100 to 1000 ppm. One of the most efficient practical method to remove phenol in waste water is adsorption. Many adsorbent can be used to adsorp phenol from waste water. In this study, coconut shell charcoal is used as the adsorbent. The adsorption kinetics of phenol in aqueous solution was studied by measuring the concentration of remaining phenol in the solution as a function of time (t) with the parameters of operation temperature (T), particle diameter of coconut shell charcoal (d), and mass ratio of coconut shell charcoal to the solution (r). The adsorption rate was found to be increased as the operation temperature and mass ratio increase, but it was decreased as the particle diameter increase. The empirical rate expression for the adsorption of phenol in aqueous solution with coconut shell charcoal has been determined as: 0,438 0,1313 1/2 0 2497,83 ln 1,4832exp C d r t C RT − ⎡ ⎤ − ⎛ ⎞ =− ⎜ ⎟ ⎢ ⎥ ⎝ ⎠ ⎣ ⎦ with the relative mean error of 30.74%. C in this equation is the phenol concentration at time t, C 0 is the concentration at t = 0, and R is the gas constant (8.314 J/mol/K). This equation is valid for the ranges of T of 303 to 333 K, d of 767 to 1879 μm, and r of 0.0476 to 0.1666, and for  the  adsorption  of  phenol  in  aqueous  solution  with  coconut  shell  charcoal  in  erlenmeyer agitated by using shaker bath.  Keywords: Adsorption Kinetics, Phenol, Aqueous Solution, Coconut Shell Charcoal